The Effect of Using Web 2.0 Tools in Algebra Teaching on Student Success and Attitude - Nayıroğlu, Buşra; Tutak, Tayfun (Tamer KUTLUCA, 2023)
This study it is aimed to examine the effect of using web 2.0 tools in algebra teaching on student achievement and attitude. The research was carried out with 42 students studying in the 6th grade of a public secondary school in Rize in the second term of the 2022-2023 academic year. In the study, in which an unequal quasi-experimental design with the pretest-posttest experiment-control group was used, there were 22 students in the experimental group and 20 students in the control group. In the study, quantitative and qualitative research designs were used together. “Algebraic Expressions Achievement Test (CIBT)” developed by Okuducu (2020) and “Attitude Scale Towards Mathematics Lesson (MDKTÖ)” developed by Baykul (1990) were used as data collection tools. In addition, the “Semi-Structured Interview Form” developed by the researchers was used. While the lesson plan containing learning activities supported by web 2.0 tools was applied to the experimental group, no intervention was made in the control group. CIBT and MDKTÖ were applied to these groups as a pre-test before the application and as a post-test after the application. In addition, at the end of each web 2.0 tools activity, the experimental group students were given opinion forms and their thoughts were taken. As a result of the statistical studies, it was concluded that the use of web 2.0 tools in algebra teaching contributed positively to the academic success of the students and positively affected the students' attitudes in mathematics teaching. In addition, when we look at the results of the semi-structured interview forms, it is concluded that algebra teaching, which is processed with web 2.0 tools, is more fun, increases interest and motivation and is permanent.

This study it is aimed to examine the effect of using web 2.0 tools in algebra teaching on student achievement and attitude. The research was carried out with 42 students studying in the 6th grade of a public secondary school in Rize in the second term of the 2022-2023 academic year. In the study, in which an unequal quasi-experimental design with the pretest-posttest experiment-control group was used, there were 22 students in the experimental group and 20 students in the control group. In the study, quantitative and qualitative research designs were used together. “Algebraic Expressions Achievement Test (CIBT)” developed by Okuducu (2020) and “Attitude Scale Towards Mathematics Lesson (MDKTÖ)” developed by Baykul (1990) were used as data collection tools. In addition, the “Semi-Structured Interview Form” developed by the researchers was used. While the lesson plan containing learning activities supported by web 2.0 tools was applied to the experimental group, no intervention was made in the control group. CIBT and MDKTÖ were applied to these groups as a pre-test before the application and as a post-test after the application. In addition, at the end of each web 2.0 tools activity, the experimental group students were given opinion forms and their thoughts were taken. As a result of the statistical studies, it was concluded that the use of web 2.0 tools in algebra teaching contributed positively to the academic success of the students and positively affected the students' attitudes in mathematics teaching. In addition, when we look at the results of the semi-structured interview forms, it is concluded that algebra teaching, which is processed with web 2.0 tools, is more fun, increases interest and motivation and is permanent.
The Effect of Using Web 2.0 Tools in Algebra Teaching on Student Success and Attitude
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar